Faktor-faktor yang berhubungan dengan Perilaku Ibu Primigravida dalam melakukan persiapan perencanaan kehamilan - Siti Nurhalimatussadiah; Eka Bati Widyaningsih; Wiwin Nur Fitriani (Politeknik Karya Husada, 2024)
In 2014, WHO stated that 4 out of 10 women had unplanned pregnancies and in Indonesia 32,000 women did not plan their pregnancies between 2010 and 2014, this number is the highest in ASEAN. Data in Indonesia shows that there has been an increase in the average value before counseling is carried out by 4.63% and after counseling has increased by 7.04% from 24 respondents.To know the factors that correlate the prinigravida mother in doing pregnancy planning. This research is analytic descriptive by cross sectional approach. Analysis Test in this research is Chi Square. Technique of collecting data used non probability with whole sampling. Sampling in this research is 43 respondents who came to Pondok Ranji public health center in January- February 2023. Based on the result of Bivariat, there was a significant correlation between outcome variable (p= 0,027), OR4,46. Family support (p= 0,004) OR= 6,69, attitude (= 0,004) OR= 6,69 and role of midwife (p= 0,002) OR= 14,06. The most dominant factor of Primigravida mothers in pregnancy planning is Midwife Role. Suggestion: Society should pay attention to pregnancy planning especially primigravida mother in pre-conception period by taking care the influenced factors, especially a midwife role. Keyword : Primigravida mother behavior, age, education, job, income, family support, attitude, midwife role.